A modified acrylic resin, preparation method, anticorrosive coating and application thereof

By using modified acrylic resin on the aluminum fins of the air-conditioning heat exchanger, combined with isocyanate modified graphene, silicon acrylic resin and hyperbranched outer layer, the problem that anticorrosion coatings in the prior art cannot take into account both corrosion resistance and high heat exchangeability, achieving high corrosion resistance and thermal conductivity of the coating, extending service life and improving heat exchange efficiency.

CN119390911BActive Publication Date: 2025-05-02GUANGZHOU HUMAN CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510013961.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-02
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The anticorrosion coatings used in the prior art for aluminum fins of air-conditioning heat exchangers cannot take into account both corrosion resistance and high heat exchange properties, resulting in aging of coatings and deterioration of corrosion in a strong corrosion environment, affecting the service life of the heat exchanger.

Method used

A modified acrylic resin is provided, including an inner core, a silicon-acre resin outer layer and a hyperbranched outer layer. The inner core is isocyanate modified graphene. A continuous barrier layer is formed by grafting the isocyanate modified graphene and the resin backbone. Combining the high bond energy of the silicon-oxygen bond and the multifunctional groups of the hyperbranched outer layer, the coating is enhanced with the corrosion resistance and thermal conductivity.

Benefits of technology

Modified acrylic resin significantly improves the corrosion resistance and thermal conductivity of the coating, extends the service life of the coating, reduces heat accumulation, improves heat exchange efficiency, and exhibits high flexibility under mechanical stress, reducing the cracking and peeling of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390911B_ABST
    Figure CN119390911B_ABST
Patent Text Reader

Abstract

In order to overcome the problem that the anticorrosive coating used for the aluminum fin of the air conditioner heat exchanger in the prior art cannot take into account both corrosion resistance and high heat exchange, a modified acrylic resin, a preparation method, an anticorrosive coating and its application are provided; the modified acrylic resin includes an inner core, a silicone-acrylic resin outer layer and a hyperbranched outer layer, the inner core is isocyanate-modified graphene, the silicone-acrylic resin outer layer is coated on the outside of the inner core, the hyperbranched outer layer is located outside the silicone-acrylic resin outer layer, and the hyperbranched outer layer is grafted with epoxy groups, amide groups and phosphate groups. The isocyanate-modified graphene in the modified acrylic resin provided by the present invention can delay the penetration of the corrosive medium into the modified acrylic resin coating, and in addition, the graphene can effectively conduct heat to improve the heat exchange efficiency; the silicone-acrylic resin outer layer and the hyperbranched outer layer isolate the substrate coated with the modified acrylic resin from the external corrosive medium through different effects; in summary, the modified acrylic resin provided by the present invention has excellent thermal conductivity and anticorrosion properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings, and specifically relates to a modified acrylic resin, a preparation method, an anti-corrosion coating and applications thereof. Background Art

[0002] The heat exchanger is one of the main components of the air conditioner and the main place for heat exchange. The most important aluminum fins are usually made of hydrophilic aluminum foil. Generally, the surface of the hydrophilic aluminum foil is coated with an anti-corrosion primer and a hydrophilic top coat. The anti-corrosion primer plays a role in protecting the substrate to prevent corrosion during use. The performance of the anti-corrosion primer determines the service life of the heat exchanger.

[0003] In a highly corrosive environment, especially in some heat exchangers located in coastal areas with high humidity, high salinity, and strong ultraviolet rays, it is very easy for the coating to corrode and the corrosion resistance to drop sharply due to coating aging, which in turn affects the weather resistance of the heat exchanger aluminum fins.

[0004] At present, improving corrosion resistance is mainly achieved by increasing the thickness of the anti-corrosion primer, but the heat exchanger used will face the following contradictions: maintaining the life of the heat exchanger → high corrosion resistance of the coating → increased coating thickness → decreased thermal conductivity of the fins → decreased heat exchange performance of the whole machine → increased power consumption, which goes against the original intention of air-conditioning companies to save energy and reduce consumption. At the same time, the increase in coating thickness will also bring difficulties to coating manufacturing and processing. The thicker the coating, the worse the flexibility and the more brittle the coating. During the high-speed punching process, the aluminum fin cut edge will be demolded, making it difficult to effectively protect the edge. At present, ordinary high-corrosion-resistant coatings cannot solve the above contradictions. In addition, since the high-corrosion-resistant system usually adopts an epoxy resin system with good corrosion resistance, the aging resistance of the epoxy resin system is difficult to guarantee, which further affects the service life of the air conditioner.

[0005] In the prior art, corrosion-resistant air-conditioning fin materials are obtained by melting, casting, hot rolling, vacuum sputtering chemical vapor deposition or vacuum evaporation. All materials are inorganic materials, but the preparation process is complicated and costly, and is not suitable for the current mainstream heat exchanger processing method; other prior arts involving anti-corrosion paints or coatings for improving thermal conductivity in other application fields are mostly spraying, shower coating, dipping, electroplating, etc. The coating thickness is thick (tens-100μm) and the uniformity cannot be fully guaranteed. Because this application field requires high-speed roller coating and the coating is relatively thin (1-5μm) and has problems with compatibility with hydrophilic surface coatings, the applicability of anti-corrosion coatings in other technical fields in air-conditioning heat exchangers is relatively poor; therefore, how to balance corrosion resistance, aging resistance and high heat transfer performance of aluminum fins of air-conditioning heat exchangers during use is a key issue that needs to be solved. Summary of the invention

[0006] Aiming at the problem that the anti-corrosion coating used for aluminum fins of air-conditioner heat exchangers in the prior art cannot take into account both corrosion resistance and high heat exchange, a modified acrylic resin, a preparation method, an anti-corrosion coating and application thereof are provided.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] On the one hand, the present invention provides a modified acrylic resin, comprising an inner core, an outer silicone-acrylic resin layer and a hyperbranched outer layer, wherein the inner core is isocyanate-modified graphene, the outer silicone-acrylic resin layer is coated on the outside of the inner core, the hyperbranched outer layer is located on the outside of the outer silicone-acrylic resin layer, and the hyperbranched outer layer is grafted with epoxy groups, amide groups and phosphate groups.

[0009] Optionally, the raw materials of the silicone-acrylic resin outer layer include acrylate monomers, acrylic acid monomers and active silicon monomers; and / or

[0010] The raw materials of the hyperbranched outer layer include a chain transfer agent, an epoxy monomer, an amide monomer and a phosphate monomer.

[0011] Optionally, the isocyanate-modified graphene includes graphene and aliphatic isocyanate grafted onto the surface of the graphene;

[0012] The number of layers of the graphene is 3-10, and the sheet diameter of the graphene is 1-3 μm.

[0013] Optionally, the aliphatic isocyanate includes one or more of isophorone diisocyanate and hexamethylene diisocyanate.

[0014] Optionally, the raw materials of the modified acrylic resin include the following mass components:

[0015] Isocyanate modified graphene 1-3 parts

[0016] Acrylate monomer 40-60 parts

[0017] 3-5 parts of acrylic monomer

[0018] Active silicon monomer 5-15 parts

[0019] Initiator 0.5-3 parts

[0020] Chain transfer agent 0.2-1 part

[0021] Epoxy monomer 3-6 parts

[0022] 2-4 parts of amide monomer

[0023] 2-6 parts of phosphate monomer.

[0024] Optionally, the acrylate monomer includes one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate, lauryl methacrylate, hydroxyethyl / propyl acrylate, hydroxyethyl / propyl methacrylate, and hydroxybutyl acrylate; and / or, the active silicon monomer includes one or more of γ-methacrylic acid acyloxyethyl / propyl trimethoxysilane, γ-vinyl trimethyl / ethoxysilane, and diethoxymethylvinyl silane; and / or, the acrylic monomer includes one or more of acrylic acid and methacrylic acid.

[0025] Optionally, the initiator includes one or more of dibenzoyl peroxide, lauroyl peroxide, and azobisisobutyronitrile; and / or, the chain transfer agent includes one or more of mercaptoethanol and dodecyl mercaptan; and / or, the epoxy monomer includes one or more of methyl / propyl acrylate and neopentanoic acid glycidyl ester; and / or, the amide monomer includes one or more of N-hydroxymethyl acrylamide, acrylamide, and diacetone acrylamide; and / or, the phosphate monomer includes one or more of SIPOMER PAM-200, PAM-300, and PAM-6000.

[0026] Optionally, the raw material of the modified acrylic resin further comprises an organic solvent, wherein the organic solvent is 30-45 parts;

[0027] The organic solvent includes one or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol butyl ether, ethylene glycol butyl ether, ethylene glycol tert-butyl ether, diethylene glycol butyl ether, diethylene glycol tert-butyl ether, ethanol, isopropanol, n-propanol, acetone, butanone, and tetrahydrofuran solution.

[0028] In another aspect, the present invention provides a method for preparing a modified acrylic resin, comprising the following steps:

[0029] S1: mixing graphene and isocyanate for dispersion reaction to obtain isocyanate-modified graphene;

[0030] S2: mixing an acrylate monomer, an acrylic acid monomer, and an active silicon monomer with an initiator to obtain a monomer mixture;

[0031] S3: taking the monomer mixture and mixing it with an organic solvent for prepolymerization to obtain a hydroxyl-containing silicone-acrylic main resin mixture;

[0032] S4: mixing the isocyanate-modified graphene, the hydroxyl-containing silicone-acrylic main resin mixture, the organic solvent and the initiator for polymerization to obtain a graphene-grafted modified hydroxyl silicone-acrylic resin mixed solution;

[0033] S5: mixing epoxy monomer, amide monomer, phosphate monomer, initiator and chain transfer agent to obtain a side chain modified monomer mixed solution;

[0034] S6: adding the side chain modified monomer mixture to the graphene grafted modified hydroxy silicone acrylic resin mixture, and then adding an initiator to react to obtain a modified acrylic resin.

[0035] On the other hand, the present invention provides an anti-corrosion coating, comprising the modified acrylic resin or the modified acrylic resin prepared by the preparation method of the modified acrylic resin.

[0036] Optionally, the anti-corrosion coating further comprises a catalyst, a neutralizer, a cross-linking agent, a leveling agent, a thickener, a light stabilizer and an ultraviolet absorber;

[0037] The catalyst is 0.1-2 parts, the neutralizer is 0.5-3 parts, the cross-linking agent is 3-10 parts, the leveling agent is 0.05-0.25 parts, the thickener is 0.5-3 parts, the light stabilizer is 0.2-0.5 parts, and the ultraviolet absorber is 0.7-1.2 parts.

[0038] Optionally, the anti-corrosion coating provided by the present invention is applied to aluminum fins of air-conditioning heat exchangers.

[0039] The beneficial effects of the present invention are:

[0040] The modified acrylic resin provided by the present invention comprises an inner core, a silicone-acrylic resin outer layer and a hyperbranched outer layer, wherein the inner core is isocyanate-modified graphene, and after the graphene is modified by isocyanate, the graphene is grafted into the main chain of the resin to form a continuous barrier layer, and the evenly distributed graphene particles form a dense network in the coating layer, which effectively delays the penetration of the corrosive medium into the modified acrylic resin coating layer; the silicon-oxygen bonds in the molecular structure of the silicone-acrylic resin outer layer have a high bond energy, so that the silicone-acrylic resin can resist the erosion of moisture and chemical substances, and effectively prevent the penetration of moisture; the epoxy groups grafted to the hyperbranched outer layer outside the silicone-acrylic resin outer layer have good chemical stability and can resist the corrosion of acidic and alkaline substances The amide groups grafted on the hyperbranched outer layer can interact with water molecules through hydrogen bonds to prevent water molecules from reacting with other components inside the modified acrylic resin. The phosphate groups can form a dense aluminum phosphate protective film with the metal surface, thereby isolating the substrate coated with the modified acrylic resin from the external corrosive medium, further improving the corrosion resistance of the coating. On the other hand, in the isocyanate-modified graphene core, the graphene can effectively conduct heat and has a high thermal conductivity, which reduces the accumulation of heat inside the coating, allowing the heat to be dissipated more efficiently, thereby improving the heat exchange efficiency. In summary, the modified acrylic resin provided by the present invention has excellent thermal conductivity and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of modified acrylate provided by the present invention;

[0042] Figure 2 It is a schematic diagram of the preparation of the anti-corrosion coating provided by the present invention. DETAILED DESCRIPTION

[0043] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] The invention provides a modified acrylic resin, comprising an inner core, a silicone-acrylic resin outer layer and a hyperbranched outer layer, wherein the inner core is isocyanate-modified graphene, the silicone-acrylic resin outer layer is coated on the outside of the inner core, the hyperbranched outer layer is located on the outside of the silicone-acrylic resin outer layer, and the hyperbranched outer layer is grafted with epoxy groups, amide groups and phosphate groups.

[0045] The modified acrylic resin provided by the present invention comprises an inner core, a silicone-acrylic resin outer layer and a hyperbranched outer layer, wherein the inner core is isocyanate-modified graphene, and after the graphene is modified by isocyanate, the graphene is grafted into the main chain of the resin to form a continuous barrier layer, and the evenly distributed graphene particles form a dense network in the coating layer, which effectively delays the penetration of the corrosive medium into the modified acrylic resin coating layer; the silicon-oxygen bonds in the molecular structure of the silicone-acrylic resin outer layer have a high bond energy, so that the silicone-acrylic resin can resist the erosion of moisture and chemical substances, and effectively prevent the penetration of moisture; the epoxy groups grafted to the hyperbranched outer layer outside the silicone-acrylic resin outer layer have good chemical stability and can resist the corrosion of acidic and alkaline substances The amide groups grafted on the hyperbranched outer layer can interact with water molecules through hydrogen bonds to prevent water molecules from reacting with other components inside the modified acrylic resin. The phosphate groups can form a dense aluminum phosphate protective film with the metal surface, thereby isolating the substrate coated with the modified acrylic resin from the external corrosive medium, further improving the corrosion resistance of the coating. On the other hand, in the isocyanate-modified graphene core, the graphene can effectively conduct heat and has a high thermal conductivity, which reduces the accumulation of heat inside the coating, allowing the heat to be dissipated more efficiently, thereby improving the heat exchange efficiency. In summary, the modified acrylic resin provided by the present invention has excellent thermal conductivity and corrosion resistance.

[0046] In addition, due to the triple helix structure between carbon atoms in graphene, it exhibits high flexibility when subjected to stress. Therefore, by modifying graphene with isocyanate and grafting it into the resin, the flexibility of the resin coating can be significantly improved, and the edge aluminum corrosion problem caused by demolding of the cut edges of the aluminum fins of the heat exchanger during high-speed punching can be reduced, thereby further enhancing the anti-corrosion performance.

[0047] In some embodiments, the raw materials of the silicone-acrylic resin outer layer include acrylate monomers, acrylic acid monomers and active silicon monomers; and / or the raw materials of the hyperbranched outer layer include chain transfer agents, epoxy monomers, amide monomers and phosphate monomers.

[0048] The acrylic monomer is one of the main components forming the outer layer of the silicone-acrylic resin, and forms a polymer main chain through polymerization. The polymer chain formed after the polymerization of the acrylic monomer has good flexibility and weather resistance. In the use environment of the aluminum fins of the air-conditioning heat exchanger, this flexibility can enable the coating to adapt to the deformation of the aluminum fins caused by temperature changes; the acrylic monomer contains active functional groups such as carboxyl groups, which participate in the polymerization reaction and adjust the properties of the polymer. The carboxyl group can increase the polarity of the polymer, which is beneficial to improve the adhesion between the resin coating and the aluminum fins or the substrate; during the polymerization process, the active silicon monomer introduces silicon elements to form silicon-oxygen bonds. The silicon-oxygen bonds have a higher bond energy, so that the coating has good water resistance and chemical corrosion resistance.

[0049] Epoxy monomers can introduce epoxy groups during the polymerization process. The epoxy groups themselves have good chemical stability and corrosion resistance, can resist the penetration of corrosive substances such as acids and alkalis, and protect the internal structure of the resin coating.

[0050] In some embodiments, the isocyanate-modified graphene includes graphene and aliphatic isocyanate grafted onto the surface of the graphene;

[0051] The number of layers of the graphene is 3-10, and the sheet diameter of the graphene is 1-3 μm.

[0052] Specifically, graphene is modified by aliphatic isocyanate and grafted into the main chain of the resin. The graphene molecules are fixed in the resin layer by chemical grafting. Compared with the physical blending of graphene in the prior art, the performance degradation and thermal stability degradation caused by graphene agglomeration can be effectively avoided; the uniformly grafted graphene particles form a continuous barrier layer in the interpenetrating network structure of the acrylic resin, which prolongs the propagation path and penetration of air and water vapor corrosion-slowing media, improves the corrosion resistance and salt spray resistance, and compared with physical dispersion, the graphene is more powerful and lasting.

[0053] Specifically, the graphene is selected from graphene oxide, more preferably graphene oxide powder. The oxidized graphene surface contains a large number of carboxyl groups, hydroxyl groups, and epoxy groups, which make the graphene have better chemical reactivity and hydrophilicity, and is easier to be evenly dispersed in the coating system. It can react chemically with the main resin group, so that the adhesion effect of graphene in the modified acrylic resin coating is better. Due to the large surface area characteristics of graphene and the structure of the two-dimensional layer, the dense network structure formed in the coating can effectively slow down the penetration of moisture, ions, and oxygen, thereby achieving high corrosion resistance.

[0054] Specifically, the number of layers of the graphene may be 3, 4, 5, 6, 7, 8, 9 or 10 layers; the sheet diameter of the graphene may be 1 μm, 2 μm or 3 μm.

[0055] In some embodiments, the aliphatic isocyanate includes one or more of isophorone diisocyanate and hexamethylene diisocyanate.

[0056] Specifically, the isocyanate groups in the aliphatic isocyanate chemically react with the hydroxyl and carboxyl groups on the graphene surface to form covalent bonds to improve the compatibility and bonding between the graphene and the resin backbone;

[0057] In a preferred embodiment, the aliphatic isocyanate is selected from isophorone diisocyanate.

[0058] In some embodiments, the raw materials of the modified acrylic resin include the following mass components:

[0059] Isocyanate modified graphene 1-3 parts

[0060] Acrylate monomer 40-60 parts

[0061] 3-5 parts of acrylic monomer

[0062] Active silicon monomer 5-15 parts

[0063] Initiator 0.5-3 parts

[0064] Chain transfer agent 0.2-1 part

[0065] Epoxy monomer 3-6 parts

[0066] 2-4 parts of amide monomer

[0067] 2-6 parts of phosphate monomer.

[0068] In some embodiments, the acrylate monomer includes one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate, lauryl methacrylate, hydroxyethyl / propyl acrylate, hydroxyethyl / propyl methacrylate, and hydroxybutyl acrylate; and / or, the active silicon monomer includes one or more of γ-methacrylic acid acyloxyethyl / propyl trimethoxysilane, γ-vinyl trimethyl / ethoxysilane, and diethoxymethylvinyl silane; and / or, the acrylic monomer includes one or more of acrylic acid and methacrylic acid.

[0069] Specifically, 5-15 parts of active silicon monomer are introduced into the modified acrylic resin. When too little active silicon monomer is introduced, the weather resistance of the silicon monomer is limited. When too much active silicon monomer is introduced, the cohesive energy density of the polysiloxane is low, the intermolecular force is small, and the surface tension of the coating is low, which affects the recoatability of the topcoat and the adhesion strength between the primer and the topcoat.

[0070] In a preferred embodiment, the acrylate monomer includes one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate, and hydroxypropyl acrylate; the active silicon monomer is selected from one or more of γ-methacrylic acid acyloxypropyl triethoxysilane, γ-vinyl trimethoxysilane, and γ-vinyl triethoxysilane; and the acrylic monomer is selected from one or more of acrylic acid and methacrylic acid.

[0071] In some embodiments, the raw material of the modified acrylic resin further comprises an organic solvent, wherein the organic solvent is 30-45 parts;

[0072] The organic solvent includes one or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol butyl ether, ethylene glycol butyl ether, ethylene glycol tert-butyl ether, diethylene glycol butyl ether, diethylene glycol tert-butyl ether, ethanol, isopropanol, n-propanol, acetone, butanone, and tetrahydrofuran solution. In some embodiments, the initiator includes one or more of dibenzoyl peroxide, lauroyl peroxide, and azobisisobutyronitrile; and / or, the chain transfer agent includes one or more of mercaptoethanol and dodecyl mercaptan; and / or, the epoxy monomer includes one or more of methyl / propyl acrylate and neodecanoic acid glycidyl ester; and / or, the amide monomer includes one or more of N-hydroxymethyl acrylamide, acrylamide, and diacetone acrylamide; and / or, the phosphate monomer includes one or more of SIPOMER PAM-200, PAM-300, and PAM-6000.

[0073] In another embodiment of the present invention, a method for preparing a modified acrylic resin is provided, comprising the following operations:

[0074] S1: mixing graphene and isocyanate for dispersion reaction to obtain isocyanate-modified graphene;

[0075] S2: mixing an acrylate monomer, an acrylic acid monomer, and an active silicon monomer with an initiator to obtain a monomer mixture;

[0076] S3: taking the monomer mixture and mixing it with an organic solvent for prepolymerization to obtain a hydroxyl-containing silicone-acrylic main resin mixture;

[0077] S4: mixing the isocyanate-modified graphene, the hydroxyl-containing silicone-acrylic main resin mixture, an organic solvent and an initiator for polymerization to obtain a graphene-grafted modified hydroxyl silicone-acrylic resin mixed solution;

[0078] S5: mixing epoxy monomer, amide monomer, phosphate monomer, initiator and chain transfer agent to obtain a side chain modified monomer mixed solution;

[0079] S6: adding the side chain modified monomer mixture to the graphene grafted modified hydroxy silicone acrylic resin mixture, and then adding an initiator to react to obtain a modified acrylic resin.

[0080] Specifically, the specific preparation method of the modified acrylic resin is as follows:

[0081] 1 part of graphene is added to tetrahydrofuran solution, ultrasonically dispersed for 1 hour, and then added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70±2°C, 99 parts of isophorone diisocyanate are dispersed in tetrahydrofuran solution, slowly added dropwise, 0.1 parts of catalyst are added, and the mixture is kept at a constant temperature for 5 hours, cooled and filtered, and the obtained solid is repeatedly washed with acetone, and then dried at 50-60°C for 12 hours to obtain isocyanate-modified graphene;

[0082] The acrylate monomer, acrylic acid monomer, active silicon monomer and initiator are stirred and pre-emulsified to obtain a monomer mixture; under nitrogen protection, the monomer mixture is added dropwise to an acetone solution at 85-90° C. and kept warm for 0.5-1 hour to obtain a hydroxyl-containing silicone-acrylic main resin mixture;

[0083] Under nitrogen protection, 1-3 parts of isocyanate-modified graphene are added to an acetone solution and ultrasonicated for 0.5 hours, then 0.2 parts of a catalyst are added, the temperature is raised to 70-75°C, and the hydroxyl silicone-acrylic main resin mixture is evenly divided into 3 parts, the first addition is reacted at a constant temperature for 2 hours, the second addition is reacted at a constant temperature for 1 hour, the third addition is stirred at a constant temperature for 0.5 hours, and then vacuum pumping is performed to remove acetone, and then 30-45 parts of an organic solvent are added to reduce the viscosity to obtain a graphene-branched modified hydroxyl silicone-acrylic resin mixed solution;

[0084] Stirring and pre-emulsifying an initiator, a chain transfer agent, an epoxy monomer, an amide monomer, and a phosphate monomer to obtain a side chain modified monomer mixed solution;

[0085] The side chain modified monomer mixture is added to the graphene grafted modified hydroxy silicone acrylic resin mixture at 110-120°C, the side chain modified monomer mixture is dripped in 1-2 hours, kept warm for 0.5-1 hour, and then the initiator is added again, kept warm for 0.5-1 hour, and cooled to 50°C to obtain a modified acrylic resin.

[0086] Specifically, the modified acrylic resin uses a hydroxy-containing silicone-acrylic main resin mixture as the main resin (from the perspective of the best weather resistance of the resin, silicone-acrylic resin is better than pure acrylic resin, better than styrene-acrylic resin, and better than commonly used epoxy resin. The si-O bond in silicone-acrylic resin is relatively stable, and it is difficult to undergo free radical reactions caused by ultraviolet rays, and it is not easy to undergo oxidation reactions, and it has good weather resistance. However, benzene and aromatic ring resins are easily broken by ultraviolet rays, and their weather resistance decreases. In addition, aliphatic or alicyclic epoxy, phosphate, amide and other functional groups are introduced into its side chain. Through the reaction between the functional groups, the cross-linking density of the resin is further increased, thereby improving the anti-corrosion performance. At the same time, H in some free functional groups is easy to form hydrogen bonds with water molecules, which can further promote the uniform dispersion of water molecules on the coating surface, and comprehensively enhance the corrosion resistance and hydrophilicity of the resin ( Figure 1 );

[0087] In addition, the introduction of active negatively charged groups on adjacent Cs can promote the interaction between metal ions and negative charges by utilizing the chelation effect to form a stable five-membered ring or six-membered ring structure, which reacts with multivalent metals to form a complex, firmly connecting the polymer to the metal substrate in the form of a covalent bond, enhancing the adhesion between the coating and the substrate, and further enhancing the anti-corrosion performance. To ensure the long-term stability of the resin, the resin and the cross-linking agent are further cured to form a hyperbranched cross-linking structure, which increases the molecular weight and further optimizes the corrosion resistance of the resin ( Figure 2 ).

[0088] Silicone monomers are introduced into the main silicone-acrylic resin. If too little silicone monomer is introduced, the improvement in weather resistance will be limited; if too much silicone monomer is introduced, the cohesive energy density of polysiloxane is low and the intermolecular force is small, so that the molecules are in a highly flexible state. This structure makes the surface tension of the coating low, which will affect the recoatability of the topcoat and the adhesion strength between the primer and the topcoat.

[0089] In another embodiment of the present invention, an anti-corrosion coating is provided, comprising the modified acrylic resin or the modified acrylic resin prepared by the preparation method of the modified acrylic resin.

[0090] Specifically, the anti-corrosion coating of the present invention mainly includes a modified acrylic resin, which includes a core, a silicone-acrylic resin outer layer and a hyperbranched outer layer. The molecular weight is increased by hyperbranched cross-linking and a dense network structure is formed, thereby enhancing the anti-corrosion performance of the modified acrylic resin. In addition, the isocyanate-modified graphene in the core of the modified acrylic resin is modified by isocyanate, and the barrier layer formed by grafting the graphene to the resin main chain effectively delays the penetration of the corrosive medium into the modified acrylic resin coating. The use of the modified acrylic resin provided by the present application to prepare the coating ensures that the coating has excellent anti-corrosion performance and weather resistance.

[0091] In some embodiments, the anti-corrosion coating further comprises a catalyst, a neutralizer, a cross-linking agent, a leveling agent, a thickener, a light stabilizer, and a UV absorber;

[0092] The catalyst is 0.1-2 parts, the neutralizer is 0.5-3 parts, the cross-linking agent is 3-10 parts, the leveling agent is 0.05-0.25 parts, the thickener is 0.5-3 parts, the light stabilizer is 0.2-0.5 parts, and the ultraviolet absorber is 0.7-1.2 parts.

[0093] Specifically, the catalyst is selected from at least one of aminosulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid and dinonylnaphthalene disulfonic acid;

[0094] The neutralizing agent is selected from one or more of ammonia water, N,N-dimethylethanolamine, triethanolamine and 2-methyl 2-aminopropanol, preferably one or more of N,N-dimethylethanolamine or triethanolamine;

[0095] The crosslinking agent is selected from one or more of amino resins, isocyanates, polycarboxylic acids and polyamines; the amino resin includes one or more of urea-formaldehyde resin, melamine-formaldehyde resin and polyamide-polyamine epichlorohydrin, more preferably melamine-formaldehyde resin;

[0096] The leveling agent is selected from one or more of an acrylic leveling agent, an organic siloxane leveling agent and an organic fluorocarbon leveling agent;

[0097] The thickener and leveling agent is selected from one or more of polyacrylate, polyurethane, inorganic and cellulose thickeners, and polyurethane is more preferred, which has good compatibility with the system and better weather resistance.

[0098] The light stabilizer is selected from one or more of hindered amine light stabilizers, quenchers, and antioxidants.

[0099] The ultraviolet absorber is selected from one or more of benzophenones, benzotriazoles, triazines and salicylates.

[0100] In some embodiments, the anti-corrosion coating is applied on aluminum fins of air conditioner heat exchangers.

[0101] Specifically, when the anti-corrosion coating prepared from modified acrylic resin is applied to the air-conditioning heat exchanger, the modified acrylic resin forms a strong chemical bond with the surface of the aluminum fin, which significantly improves the adhesion of the coating, prevents the coating from falling off or peeling off during use, and ensures long-term anti-corrosion effect. In addition, by grafting graphene, the coating exhibits high flexibility when subjected to external force impact, reduces the cracking and peeling of the coating caused by mechanical stress, and further improves the overall protective performance of the aluminum fin. At the same time, the addition of graphene not only enhances the anti-corrosion performance, but also improves the thermal conductivity of the paint coating, which helps the aluminum fins to dissipate heat more efficiently and avoids the problem of a sharp drop in heat transfer due to coating damage. The improvement in thermal conductivity is also conducive to improving the heat transfer efficiency of the aluminum fins, thereby achieving the purpose of energy saving and consumption reduction.

[0102] The present invention is further described below by way of examples.

[0103] Example 1

[0104] This embodiment is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes the following operations:

[0105] Preparation of modified acrylic resin:

[0106] One part of graphene oxide with four layers and a sheet diameter of 2 μm was added to a tetrahydrofuran solution, and after ultrasonic dispersion for 1 hour, it was added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70°C. 99 parts of isophorone diisocyanate were dispersed in the tetrahydrofuran solution and slowly added dropwise over 1 hour. 0.1 parts of stannous isooctanoate catalyst was added, and after keeping the temperature constant for 5 hours, the solid was cooled and filtered, and washed repeatedly with acetone, and then dried in a vacuum drying oven at 50°C for 12 hours to obtain an isocyanate-modified graphene active body.

[0107] 25 parts of methyl methacrylate, 10 parts of butyl acrylate, 5 parts of isooctyl acrylate, 10 parts of hydroxyethyl methacrylate, 3 parts of methacrylic acid, 10 parts of γ-methacrylic acid acyloxypropyl trimethoxysilane, and 1.4 parts of initiator were stirred and pre-emulsified to obtain a monomer mixture;

[0108] Under nitrogen protection, the monomer mixture was added dropwise to an acetone solution at 85°C over a period of 3 hours. After the reaction was completed, the mixture was kept warm for 0.5 hours to obtain a hydroxy-containing silicone-acrylic main resin mixture.

[0109] Under nitrogen protection, 1.5 parts of isocyanate-modified graphene were added to an acetone solution and ultrasonicated for 0.5 hours, and then 0.2 parts of stannous isooctanoate catalyst were added, and the temperature was raised to 70°C. The hydroxyl silicone-acrylic main resin mixture was evenly divided into 3 parts, and the first addition was reacted at a constant temperature for 2 hours, the second addition was reacted at a constant temperature for 1 hour, and the third addition was stirred at a constant temperature for 0.5 hours. After the reaction was completed, vacuum extraction was performed to remove acetone, and then 40 parts of ethylene glycol butyl ether were added to reduce the viscosity to obtain a graphene-grafted hydroxyl silicone-acrylic resin mixture;

[0110] 0.2 parts of dibenzoyl peroxide, 0.3 parts of mercaptoethanol, 3 parts of glycidyl acrylate, 3 parts of N-hydroxymethyl acrylamide and SIPOMER PAM-6000 were stirred and pre-emulsified to obtain a side chain modified monomer mixture;

[0111] The side chain modified monomer mixture was added dropwise to the graphene grafted modified hydroxy silicone acrylic resin mixture at 110°C. The side chain modified monomer mixture was added completely within 1 hour and kept warm for 0.5 hours. Then 0.4 parts of initiator were added and kept warm for another 1 hour. The modified acrylic resin was obtained by cooling to 50°C.

[0112] Preparation of anti-corrosion coatings:

[0113] Take 20 parts of deionized water, 2 parts of neutralizer, 0.2 parts of catalyst, 35 parts of modified acrylic resin, 7 parts of crosslinking, 0.2 parts of light stabilizer, 1 part of ultraviolet absorber, 0.1 parts of leveling agent, 1 part of thickener, and make up the balance with ionized water, stir and mix evenly, and prepare an anticorrosive coating with a solid content of 26.5%;

[0114] Preparation of hydrophilic aluminum foil coating:

[0115] On 0.105mm thick aluminum foil substrate, dry film weight 2.5g / m 2 Plate making, baking at 280℃ / 20s, and then baking at 280 / 30s, and then coating again with a layer of dry film weight of 0.3g / m 2 A hydrophilic aluminum foil coating is prepared by coating the hydrophilic surface.

[0116] Example 2

[0117] This embodiment is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes the following operations:

[0118] Preparation of modified acrylic resin:

[0119] One part of graphene oxide with 6 layers and a flake diameter of 3 μm was added to a tetrahydrofuran solution, and after ultrasonic dispersion for 1 hour, it was added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70°C. 99 parts of isophorone diisocyanate were dispersed in the tetrahydrofuran solution and slowly added dropwise for 1 hour. 0.1 parts of stannous isooctanoate catalyst was added, and after keeping the temperature constant for 5 hours, the solid was cooled and filtered, and washed repeatedly with acetone, and then dried in a 50°C vacuum drying oven for 12 hours to obtain isocyanate-modified graphene.

[0120] 20 parts of methyl methacrylate, 5 parts of acrylonitrile, 9 parts of butyl acrylate, 6 parts of isooctyl acrylate, 6 parts of hydroxypropyl acrylate, 4 parts of acrylic acid, 7 parts of γ-methacryloyloxypropyl triethoxysilane, and 0.7 parts of initiator were stirred and pre-emulsified to obtain a monomer mixture;

[0121] Under nitrogen protection, the monomer mixture was added dropwise to an acetone solution at 85°C over a period of 2.5 hours. After the reaction was completed, the mixture was kept warm for 1 hour to obtain a hydroxy-containing silicone-acrylic main resin mixture.

[0122] Under nitrogen protection, 1 part of isocyanate-modified graphene was added to an acetone solution and ultrasonicated for 0.5h, then 0.2 parts of stannous isooctanoate catalyst was added, the temperature was raised to 70°C, and the hydroxy-containing silicone-acrylic main resin mixture was evenly divided into 3 parts, and the first addition was reacted at a constant temperature for 2h, the second addition was reacted at a constant temperature for 1h, and the third addition was stirred at a constant temperature for 0.5h. After the reaction was completed, vacuum extraction was performed to remove acetone, and then 35 parts of ethylene glycol butyl ether were added to reduce the viscosity to obtain a graphene-branched modified hydroxy-containing silicone-acrylic resin mixture;

[0123] 0.15 parts of dibenzoyl peroxide, 0.5 parts of mercaptoethanol, 5 parts of glycidyl methacrylate, 2 parts of acrylamide, and SIPOMER PAM-200 were stirred and pre-emulsified to obtain a side chain modified monomer mixture;

[0124] The side chain modified monomer mixture was added dropwise to the graphene grafted modified hydroxy silicone acrylic resin mixture at 115°C. The side chain modified monomer mixture was added completely within 1 hour and kept warm for 0.5 hours. Then 0.15 parts of initiator were added and kept warm for another 1 hour. The temperature was lowered to 50°C to obtain the modified acrylic resin.

[0125] Preparation of anti-corrosion coatings:

[0126] Take 17 parts of deionized water, 1.5 parts of neutralizer, 0.3 parts of catalyst, 30 parts of modified acrylic resin, 6 parts of crosslinking agent, 0.5 parts of light stabilizer, 1 part of ultraviolet absorber, 0.2 parts of leveling agent, 1 part of thickener, and make up the balance with ionized water, stir and mix evenly, and prepare an anticorrosive coating with a solid content of 27.5%;

[0127] Preparation of hydrophilic aluminum foil coating:

[0128] On 0.105mm thick aluminum foil substrate, dry film weight 3g / m 2 Plate making, baking at 280℃ / 25s, and then baking at 280 / 25s again, coating with a layer of dry film weight of 0.25g / m 2 A hydrophilic aluminum foil coating is prepared by coating the hydrophilic surface.

[0129] Example 3

[0130] This embodiment is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes the following operations:

[0131] Preparation of modified acrylic resin:

[0132] One part of graphene oxide with 7 layers and a sheet diameter of 1 μm was added to a tetrahydrofuran solution, and after ultrasonic dispersion for 1 hour, it was added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70°C. 99 parts of isophorone diisocyanate were dispersed in the tetrahydrofuran solution and slowly added dropwise for 1 hour. 0.1 parts of stannous isooctanoate catalyst was added, and after keeping the temperature constant for 5 hours, the solid was cooled and filtered, and washed repeatedly with acetone, and then dried in a 50°C vacuum drying oven for 12 hours to obtain isocyanate-modified graphene.

[0133] 24 parts of methyl methacrylate, 6 parts of acrylonitrile, 8 parts of butyl acrylate, 7.5 parts of isooctyl acrylate, 8 parts of hydroxypropyl acrylate, 4 parts of acrylic acid, 12 parts of γ-vinyltriethoxysilane, and 0.7 parts of initiator were stirred and pre-emulsified to obtain a monomer mixture;

[0134] Under nitrogen protection, the monomer mixture was added dropwise to an acetone solution at 85°C over a period of 2.5 hours. After the reaction was completed, the mixture was kept warm for 1 hour to obtain a hydroxy-containing silicone-acrylic main resin mixture.

[0135] Under nitrogen protection, 1 part of isocyanate-modified graphene was added to an acetone solution and ultrasonicated for 0.5h, then 0.2 parts of stannous isooctanoate catalyst was added, the temperature was raised to 70°C, and the hydroxyl silicone-acrylic main resin mixture was evenly divided into 3 parts, the first addition was reacted at a constant temperature for 2h, the second addition was reacted at a constant temperature for 1h, and the third addition was stirred at a constant temperature for 0.5h. After the reaction was completed, vacuum extraction was performed to remove acetone, and then 30 parts of ethylene glycol butyl ether were added to reduce the viscosity to obtain a graphene-branched modified hydroxyl silicone-acrylic resin mixture;

[0136] 0.15 parts of dibenzoyl peroxide, 0.7 parts of mercaptoethanol, 6 parts of glycidyl methacrylate, 3 parts of acrylamide, and SIPOMER PAM-300 were stirred and pre-emulsified to obtain a side chain modified monomer mixture;

[0137] The side chain modified monomer mixture was added dropwise to the graphene grafted modified hydroxy silicone acrylic resin mixture at 120°C. The side chain modified monomer mixture was added completely within 1 hour and kept warm for 0.5 hours. Then 0.15 parts of initiator were added and kept warm for another 1 hour. The temperature was lowered to 50°C to obtain the modified acrylic resin.

[0138] Preparation of anti-corrosion coatings:

[0139] Take 17 parts of deionized water, 2.5 parts of neutralizer, 0.25 parts of catalyst, 40 parts of modified acrylic resin, 8.5 parts of crosslinking agent, 0.3 parts of light stabilizer, 1.2 parts of ultraviolet absorber, 0.1 parts of leveling agent, 2 parts of thickener, and make up the balance with ionized water, stir and mix evenly, and prepare an anticorrosive coating with a solid content of 29%;

[0140] Preparation of hydrophilic aluminum foil coating:

[0141] On 0.105mm thick aluminum foil substrate, dry film weight 4g / m 2 The board was baked at 280℃ / 30s, and then baked at 280 / 25s and coated again with a dry film weight of 0.25g / m 2 A hydrophilic aluminum foil coating is prepared by coating the hydrophilic surface.

[0142] Example 4

[0143] This embodiment is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes the following operations:

[0144] Preparation of modified acrylic resin:

[0145] One part of graphene oxide with three layers and a flake diameter of 2 μm was added to a tetrahydrofuran solution, and after ultrasonic dispersion for 1 hour, it was added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70°C. 99 parts of isophorone diisocyanate were dispersed in the tetrahydrofuran solution and slowly added dropwise for 1 hour. 0.1 parts of stannous isooctanoate catalyst was added, and after keeping the temperature constant for 5 hours, the solid was cooled and filtered, and washed repeatedly with acetone, and then dried in a 50°C vacuum drying oven for 12 hours to obtain isocyanate-modified graphene.

[0146] 30 parts of methyl methacrylate, 4 parts of acrylonitrile, 9 parts of butyl acrylate, 6 parts of isooctyl acrylate, 8 parts of hydroxypropyl acrylate, 4 parts of methacrylic acid, 15 parts of γ-vinyltrimethoxysilane, and 2.1 parts of initiator were stirred and pre-emulsified to obtain a monomer mixture;

[0147] Under nitrogen protection, the monomer mixture was added dropwise to an acetone solution at 85°C over a period of 2.5 hours. After the reaction was completed, the mixture was kept warm for 1 hour to obtain a hydroxy-containing silicone-acrylic main resin mixture.

[0148] Under nitrogen protection, 2 parts of isocyanate-modified graphene were added to an acetone solution and ultrasonicated for 0.5 hours, and then 0.2 parts of stannous isooctanoate catalyst was added, and the temperature was raised to 70°C. The hydroxyl silicone-acrylic main resin mixture was evenly divided into 3 parts, and the first addition was reacted at a constant temperature for 2 hours, the second addition was reacted at a constant temperature for 1 hour, and the third addition was stirred at a constant temperature for 0.5 hours. After the reaction was completed, vacuum extraction was performed to remove acetone, and then 30 parts of ethylene glycol butyl ether were added to reduce the viscosity to obtain a graphene-branched modified hydroxyl silicone-acrylic resin mixture;

[0149] 0.6 parts of dibenzoyl peroxide, 1 part of mercaptoethanol, 5 parts of neodecanoic acid glycidyl ester, 3 parts of diacetone acrylamide, and SIPOMER PAM-6000 were stirred and pre-emulsified to obtain a side chain modified monomer mixture;

[0150] The side chain modified monomer mixture was added dropwise to the graphene grafted modified hydroxy silicone acrylic resin mixture at 110°C. The side chain modified monomer mixture was added completely within 1 hour and kept warm for 0.5 hours. Then 0.3 parts of initiator were added and kept warm for another 1 hour. The mixture was cooled to 50°C to obtain the modified acrylic resin.

[0151] Preparation of anti-corrosion coatings:

[0152] Take 30 parts of deionized water, 2.5 parts of neutralizer, 0.4 parts of catalyst, 25 parts of modified acrylic resin, 8 parts of crosslinking agent, 0.3 parts of light stabilizer, 0.7 parts of ultraviolet absorber, 0.3 parts of leveling agent, 0.5 parts of thickener, and make up the balance with ionized water, stir and mix evenly, and prepare an anticorrosive coating with a solid content of 25%;

[0153] Preparation of hydrophilic aluminum foil coating:

[0154] On 0.105mm thick aluminum foil substrate, dry film weight 3g / m 2 Plate making, baking at 280℃ / 30s, and then baking at 280 / 25s, and then coating again with a layer of dry film weight of 0.2g / m 2 A hydrophilic aluminum foil coating is prepared by coating the hydrophilic surface.

[0155] Example 5

[0156] This embodiment is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes the following operations:

[0157] Preparation of modified acrylic resin:

[0158] One part of graphene oxide with 5 layers and a flake diameter of 2 μm was added to tetrahydrofuran solution, ultrasonically dispersed for 1 hour, and then added to a four-necked flask under nitrogen protection, heated and kept at a constant temperature of 70°C. 99 parts of isophorone diisocyanate were dispersed in the tetrahydrofuran solution and slowly added dropwise for 1 hour. 0.1 parts of stannous isooctanoate catalyst was added, and the mixture was kept at a constant temperature for 5 hours. The obtained solid was cooled and filtered, washed repeatedly with acetone, and dried in a 50°C vacuum drying oven for 12 hours to obtain isocyanate-modified graphene.

[0159] 25 parts of methyl methacrylate, 2 parts of acrylonitrile, 7 parts of butyl acrylate, 5 parts of isooctyl acrylate, 10 parts of hydroxypropyl acrylate, 3 parts of methacrylic acid, 10 parts of γ-vinyltriethoxysilane, and 1.4 parts of initiator were stirred and pre-emulsified to obtain a monomer mixture;

[0160] Under nitrogen protection, the monomer mixture was added dropwise to an acetone solution at 85°C over a period of 3 hours. After the reaction was completed, the mixture was kept warm for 0.5 hours to obtain a hydroxy-containing silicone-acrylic main resin mixture.

[0161] Under nitrogen protection, 3 parts of isocyanate-modified graphene were added to an acetone solution and ultrasonicated for 0.5 hours, and then 0.2 parts of stannous isooctanoate catalyst was added, and the temperature was raised to 70°C. The hydroxyl silicone-acrylic main resin mixture was evenly divided into 3 parts, and the first addition was reacted at a constant temperature for 2 hours, the second addition was reacted at a constant temperature for 1 hour, and the third addition was stirred at a constant temperature for 0.5 hours. After the reaction was completed, vacuum extraction was performed to remove acetone, and then 30 parts of ethylene glycol butyl ether were added to reduce the viscosity to obtain a graphene-branched modified hydroxyl silicone-acrylic resin mixture;

[0162] 0.4 parts of dibenzoyl peroxide, 0.8 parts of mercaptoethanol, 5 parts of glycidyl methacrylate, 3 parts of diacetone acrylamide, and SIPOMER PAM-300 were stirred and pre-emulsified to obtain a side chain modified monomer mixture;

[0163] The side chain modified monomer mixture was added dropwise to the graphene grafted modified hydroxy silicone acrylic resin mixture at 120°C. The side chain modified monomer mixture was added completely within 1 hour and kept warm for 0.5 hours. Then 0.2 parts of initiator were added and kept warm for another 1 hour. The temperature was lowered to 50°C to obtain the modified acrylic resin.

[0164] Preparation of anti-corrosion coatings:

[0165] Take 30 parts of deionized water, 1.5 parts of neutralizer, 1 part of catalyst, 27 parts of modified acrylic resin, 10 parts of crosslinking agent, 0.2 parts of light stabilizer, 1 part of ultraviolet absorber, 0.1 parts of leveling agent, 1.5 parts of thickener, and make up the balance with ionized water, stir and mix evenly, and prepare an anticorrosive coating with a solid content of 26%;

[0166] Preparation of hydrophilic aluminum foil coating:

[0167] On 0.105mm thick aluminum foil substrate, dry film weight 2g / m 2 The board was baked at 280℃ / 25s, and then baked at 280 / 30s and coated again with a dry film weight of 0.2g / m 2 A hydrophilic aluminum foil coating is prepared by coating the hydrophilic surface.

[0168] Example 6

[0169] This example is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 3, except that:

[0170] Preparation of hydrophilic aluminum foil coating:

[0171] On 0.105mm thick aluminum foil substrate, dry film weight 6g / m 2 Plate making.

[0172] Example 7

[0173] This example is used to illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 3, except that:

[0174] Preparation of hydrophilic aluminum foil coating:

[0175] On 0.105mm thick aluminum foil substrate, dry film weight 1g / m 2 Plate making.

[0176] Comparative Example 1

[0177] This comparative example is used to compare and illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 1, except that:

[0178] The outer layer of the silicone-acrylic resin in the modified acrylic resin is not modified with active silicone monomer.

[0179] Comparative Example 2

[0180] This comparative example is used to compare and illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 1, except that:

[0181] The hyperbranched outer layer of the modified acrylic resin is grafted with monomers without side chains (epoxy, amide, phosphate).

[0182] Comparative Example 3

[0183] This comparative example is used to compare and illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 1, except that:

[0184] The modified acrylic resin core graphene was not modified with isocyanate.

[0185] Comparative Example 4

[0186] This comparative example is used to compare and illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 1, except that:

[0187] The outer layer of the silicone-acrylic resin in the modified acrylic resin is not modified with active silicon monomers, and the number of graphene layers in the inner core is 15 and the sheet diameter is 10 μm.

[0188] Comparative Example 5

[0189] This comparative example is used to compare and illustrate a modified acrylic resin, a preparation method and an anticorrosive coating disclosed in the present invention, and includes most of the operations in Example 1, except that:

[0190] Ordinary graphene that has not been modified with isocyanate is added by physical blending.

[0191] Performance Testing

[0192] The relevant performance tests were performed on the Examples 1-7 and Comparative Examples 1-5 prepared above:

[0193] Hydrophilicity: GB / T 22638.9 method

[0194] Solvent resistance: Wipe with butanone according to GB / T 8753.4

[0195] Adhesion: GB / T 9286 method

[0196] Thermal conductivity: Tested according to the following formula

[0197] ;

[0198] λ: Thermal conductivity of the sample, W / m·K

[0199] Qh: heat flux output of the thermal sensor above, W / m2

[0200] Qc: heat flux output of the underlying thermal sensor, W / m2

[0201] L: thickness of the sample, m

[0202] ΔT: Temperature difference between the upper and lower surfaces of the sample, K.

[0203] Neutral salt spray resistance: The specimen is not scribed and is tested according to the neutral salt spray test method specified in GB / T 12967.3. The test results are evaluated in accordance with the provisions of GB / T 42514.

[0204] Weather resistance: in accordance with the weather resistance test requirements of YS / T 95.2-2020;

[0205] Flexibility: Test according to GB / T 12967.5 and bend using a bending machine.

[0206] The test results obtained are entered in Table 1.

[0207] Table 1

[0208]

[0209] From the test results in Table 1, it can be seen that compared with Comparative Example 1, in the preparation of modified acrylic resin, the outer layer of the silicone-acrylic resin of Comparative Example 1 was not modified with active silicone monomers. From the specific test results of the two, it can be seen that in the weather resistance test and the anti-corrosion after weathering test of Comparative Example 1, the coating had a discoloration problem and the anti-corrosion after weathering decreased, proving that the acrylic resin that has not been modified with silicone monomers is not conducive to the improvement of weather resistance and anti-corrosion performance after weathering after coating; Compared with Comparative Example 2, in Examples 1-7, the resin has no side chain group modification, and the degree of hyperbranching cannot be achieved, so the cross-linking curing group is reduced, so that the solvent resistance test result of the coating after coating becomes worse, further causing the decline of anti-corrosion performance;

[0210] Compared with Comparative Example 3, in Examples 1-5, the graphene in the modified acrylic resin core of Comparative Example 3 is not modified with isocyanate, and only a few reactive groups can graft the graphene into the main chain of the resin, and the graphene agglomerates, resulting in decreased leveling and hydrophilicity. Therefore, the thermal conductivity and corrosion resistance of the coating prepared by the resin provided in Comparative Example 3 are not significantly improved;

[0211] Compared with Comparative Example 1, the thermal conductivity of Comparative Example 4 is significantly reduced. The reason is that when the amount of graphene added in Comparative Example 4 is small and the number of layers and the sheet diameter are large, the thermal conductivity is not significantly improved, and the corrosion resistance is not significantly improved;

[0212] Compared with Comparative Example 5, Embodiments 1-5 are different from the present invention in that the graphene is modified by isocyanate and then chemically grafted with modified resin. The comparative example simply adopts physical blending to add ordinary graphene, and the graphene is unevenly dispersed and easily agglomerated, resulting in decreased hydrophilicity, and the thermal conductivity and corrosion resistance cannot be effectively improved.

[0213] Compared with Example 3, the overall performance test results of Example 6 are relatively poor, and Example 7 is second. The reason is that when preparing the coating in Example 6, the dry film weight on the foil is 6g / m 2 , and the dry film weight on the foil in the example preparation is 4g / m 2Compared with the above, the coating amount is higher, so the performance in the tests of construction, leveling and flexibility is poor, while the dry film weight on the foil of Example 7 is 1g / m 2 , compared with Example 4, the coating amount is relatively small, and its performance in thermal conductivity and weather resistance is slightly lower than that in Example 3.

[0214] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified acrylic resin, characterized in that: It comprises an inner core, an outer layer of silicone-acrylic resin and a hyperbranched outer layer, wherein the raw material of the inner core is isocyanate-modified graphene, the raw material of the outer layer of silicone-acrylic resin comprises acrylate monomers, acrylic acid monomers and active silicon monomers, and the outer layer of silicone-acrylic resin is coated on the outside of the inner core; The core raw material reacts with the silicone-acrylic resin outer layer raw material to obtain a graphene-grafted modified hydroxy silicone-acrylic resin; The hyperbranched outer layer is located outside the silicone-acrylic resin outer layer, and the hyperbranched outer layer is grafted with epoxy groups, amide groups and phosphate groups.

2. A modified acrylic resin according to claim 1, wherein the raw materials of the hyperbranched outer layer include a chain transfer agent, an epoxy monomer, an amide monomer and a phosphate monomer.

3. A modified acrylic resin according to claim 1, characterized in that: The isocyanate-modified graphene includes graphene and aliphatic isocyanate grafted on the surface of the graphene; The number of layers of the graphene is 3-10, and the sheet diameter of the graphene is 1-3 μm.

4. A modified acrylic resin according to claim 3, characterized in that: The aliphatic isocyanate includes one or more of isophorone diisocyanate and hexamethylene diisocyanate.

5. A modified acrylic resin according to claim 2, characterized in that: The raw materials of the modified acrylic resin include the following mass components: Isocyanate modified graphene 1-3 parts Acrylate monomer 40-60 parts 3-5 parts of acrylic monomer Active silicon monomer 5-15 parts Initiator 0.5-3 parts Chain transfer agent 0.2-1 part Epoxy monomer 3-6 parts 2-4 parts of amide monomer 2-6 parts of phosphate monomer.

6. A modified acrylic resin according to claim 5, characterized in that: The acrylic acid ester monomers include one or more of methyl methacrylate, butyl acrylate, isooctyl acrylate, lauryl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl acrylate; and / or, the active silicon monomers include one or more of γ-methacryloyloxyethyl trimethoxysilane, γ-methacryloyloxypropyl trimethoxysilane, γ-vinyl trimethoxysilane, γ-vinyl triethoxysilane, and diethoxymethyl vinyl silane; and / or, the acrylic acid monomers include one or more of The monomer includes one or more of acrylic acid and methacrylic acid; and / or, the initiator includes one or more of dibenzoyl peroxide, lauroyl peroxide, and azobisisobutyronitrile; and / or, the chain transfer agent includes one or more of mercaptoethanol and dodecyl mercaptan; and / or, the epoxy monomer includes one or more of glycidyl methacrylate and glycidyl neodecanoate; and / or, the amide monomer includes one or more of N-hydroxymethyl acrylamide, acrylamide, and diacetone acrylamide; and / or, the phosphate monomer includes one or more of SIPOMER PAM-200, PAM-300, and PAM-6000; The raw material of the modified acrylic resin also includes an organic solvent, wherein the organic solvent is 30-45 parts; The organic solvent includes one or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol butyl ether, ethylene glycol butyl ether, ethylene glycol tert-butyl ether, diethylene glycol butyl ether, diethylene glycol tert-butyl ether, ethanol, isopropanol, n-propanol, acetone, butanone, and tetrahydrofuran solution.

7. The method for preparing the modified acrylic resin according to any one of claims 1 to 6, characterized in that: The following operations are included: S1: mixing graphene and isocyanate for dispersion reaction to obtain isocyanate-modified graphene; S2: mixing an acrylate monomer, an acrylic acid monomer, and an active silicon monomer with an initiator to obtain a monomer mixture; S3: taking the monomer mixture and mixing it with an organic solvent for prepolymerization to obtain a hydroxyl-containing silicone-acrylic main resin mixture; S4: mixing the isocyanate-modified graphene, the hydroxyl-containing silicone-acrylic main resin mixture, the organic solvent and the initiator for polymerization to obtain a graphene-grafted modified hydroxyl silicone-acrylic resin mixed solution; S5: mixing epoxy monomer, amide monomer, phosphate monomer, initiator and chain transfer agent to obtain a side chain modified monomer mixed solution; S6: adding the side chain modified monomer mixture to the graphene grafted modified hydroxy silicone acrylic resin mixture, and then adding an initiator to react to obtain a modified acrylic resin.

8. An anticorrosive coating, characterized in that: The modified acrylic resin comprises the modified acrylic resin according to any one of claims 1 to 6 or the modified acrylic resin prepared by the preparation method of the modified acrylic resin according to claim 7.

9. The anti-corrosion coating according to claim 8, characterized in that: The anticorrosive coating also includes a catalyst, a neutralizer, a cross-linking agent, a leveling agent, a thickener, a light stabilizer and an ultraviolet absorber; The catalyst is 0.1-2 parts, the neutralizer is 0.5-3 parts, the cross-linking agent is 3-10 parts, the leveling agent is 0.05-0.25 parts, the thickener is 0.5-3 parts, the light stabilizer is 0.2-0.5 parts, and the ultraviolet absorber is 0.7-1.2 parts.

10. The anti-corrosion coating according to claim 8 is applied to aluminum fins of air conditioner heat exchangers.

Citation Information

Patent Citations

  • Acrylic emulsion with self-crosslinked core-shell structure, and preparation method of acrylic emulsion

    CN106977654A

  • Graphene-modified water-based silicone-acrylic multi-functional emulsion and preparation method thereof

    CN109608588A